1998
DOI: 10.1902/jop.1998.69.11.1263
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Porphyromonas gingivalis 2561 Extracts on Osteogenic and Osteoclastic Cell Function in Co‐Culture

Abstract: This study was undertaken to determine the direct effects of extracts derived from Porphyromonas gingivalis on bone formation and mineral resorption in an osteogenic/osteoclastic cell in vitro co‐culture model. Osteogenic bone marrow derived stromal cells were isolated from 18‐day old embryonic chickens, while osteoclastic cells were isolated from laying white Leghorn hens on calcium deficient diets. Osteoclastic cells (5 × 105) were seeded onto mineral thin films and suspended above osteogenic cells (1 × 104)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Investigations focused on determining regulators of tooth/periodontal development often use rodents and follow molar and/or incisor development (5,29,56,96,135,140,143,187,192,232,236,237,240,253). In vitro models include cell cultures where cells are obtained from animal tissues and cells can be manipulated in various ways to mimic the in vivo environment, such as growing cells on or within selective matrices or using a variety of co-culture models (49, 69,117,132,168). While in vivo models reflect the complexities of host-cell interactions, and thus may more accurately reflect the regenerative activities in humans (80), versus in vitro models, there are significant limitations.…”
Section: Models To Study Cementogenesismentioning
confidence: 99%
“…Investigations focused on determining regulators of tooth/periodontal development often use rodents and follow molar and/or incisor development (5,29,56,96,135,140,143,187,192,232,236,237,240,253). In vitro models include cell cultures where cells are obtained from animal tissues and cells can be manipulated in various ways to mimic the in vivo environment, such as growing cells on or within selective matrices or using a variety of co-culture models (49, 69,117,132,168). While in vivo models reflect the complexities of host-cell interactions, and thus may more accurately reflect the regenerative activities in humans (80), versus in vitro models, there are significant limitations.…”
Section: Models To Study Cementogenesismentioning
confidence: 99%
“…Local delivery of Poly (P) may have adjunctive benefits in the treatment of periodontitis as part of a prescription safety programme, as Poly (P) was Table 2 Age (yr) of the patients who improved at the 2nd visit. GI Poly (P) 57.2 ± 4.8 (6) 51.4 ± 9.6 (11) 51.3 ± 9.2 (12) 49.5 ± 10.9 (13) 49.5 ± 10.9 (13) 49.5 ± 10.9 (13) 49.2 ± 11.9 (11) 51.3 ± 12.1 (18) Control 48.6 ± 14.4 (5) 53.0 ± 11.5 (11) 54.2 ± 13.0 (11) 55.9 ± 12.7 (13) 57.5 ± 13.5 (13) 53.1 ± 14.0 (12) 51.2 ± 13.0 (11) 56.0 ± 12.9 (9) p-value 0. Table 3 Age (yr) of the patients who did not improve at the 2nd visit.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, antibiotic‐resistance genes are not uncommon in Gram‐negative anaerobes, such as Porphyromonas gingivalis 14,15 . The administration was explained by the fact that osteoblastic differentiation is inhibited by extracts obtained from periodontopathic bacteria, including P. gingivalis 16–20 , which is present in the ‘plaque‐free zone’ associated with biofilm formation at the bottom of human periodontal pockets 21 . However, regeneration is not easy using antimicrobial therapy in chronic periodontitis alone and therefore, a new biological treatment approach is needed.…”
Section: Introductionmentioning
confidence: 99%
“…16 Moreover, it was reported that osteoblastic differentiation could be inhibited by extracts obtained from periodontopathic bacteria including P. gingivalis, but the inhibitory effect of these bacterial extracts was blocked by indomethacin, a known inhibitor of endogenous PGE 2 production. 18,30 Therefore, we investigated the effects of pretreatment with SPEs on the amount of We intend to conduct further studies concerning the change in BMP receptors and signal transduction to understand the underlying mechanisms involved in the P.…”
Section: A the Effects Of Spes On The Alp Activity Of Mco Cellsmentioning
confidence: 99%
“…These facts suggest that P.gingivalis not only stimulates osteoclastic activity but also inhibits osteoblastic activity. 18,[28][29][30][31] Therefore, it is possible that the above mentioned biologic activities of BMPs also could be modified by periodontopathic bacteria. The purpose of this study was to examine whether rhBMP-4 could exert a stimulatory effect on the differentiation of primary mouse calvarial osteoblstic(MCO) cells which were affected by P. gingivalis.…”
mentioning
confidence: 99%